Insiden Pneumotoraks setelah Prosedur Intervensi Paru: Systematic Review - Syabila Andini; Gemilang Khusnurrokhman (Lombok Medical Journal, 2026)
Diagnostic management of peripheral lung lesions and diffuse lung parenchymal disease faces major challenges in balancing diagnostic accuracy with the risk of complications. Pneumothorax is the most frequently reported iatrogenic complication and can increase morbidity, the need for emergency intervention, and patient length of hospital stay. This study aims to systematically evaluate the incidence of pneumothorax and the requirement for thoracic drainage in various lung intervention methods to provide safety-focused procedural selection guidance. This systematic review was prepared following PRISMA guidelines with a comprehensive literature search on PubMed, Cochrane Library, and Frontiers databases. Analysis revealed significant risk variation between intervention methods. CT-guided percutaneous transthoracic lung biopsy (CT-PTLB) procedures showed the highest risk, with pneumothorax rates reaching 25.9% and chest tube requirements at 6.9%. Conversely, transbronchial techniques offer a better safety profile, where conventional transbronchial lung biopsy has a pneumothorax incidence of 1-6%, r-EBUS approximately 1.4-5.0%, and transbronchial cryobiopsy between 6-10%. Risk factors such as emphysema, lesion depth >2 cm, and the use of larger needle sizes (18G) were identified as strong predictors of pneumothorax. Selection of the appropriate technique and patient positioning (biopsy-side down) are highly recommended to minimize complications while maintaining patient safety.